TUNJUK AJAR PANTUN ULU JAMBAU DESA PASIR SIALANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Muzny, Ilmy Mulky; Syafrial, Syafrial; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research departs from teaching instruction in the pantun ulu jambau. The problem that arises is what is the point of teaching that is found in the pantun ulu jambau. The aim of this study is to describe the teaching points found in the pantun ulu jambau. The benefits of this study are divided into three, namely theoretical, practical and educational. The research method used is a qualitative method that describes descriptive data. Data collection techniques used are literature studies and enriched with interviews. The type of research used is qualitative with descriptive method. The data sources in this research are pantun ulu jambau by datuk patido ajo. The validity technique of data using persistence techniques in observing perseverance in meaning means searching for interpretations consistently in various ways, namely by acting on the psychic resource person and with a constant analysis process. reference material pantun ulu jambau works datuk patido ajo researchers focus on teaching points (obedience to 9 data leaders), (deliberation and consensus 4 data), (modesty 4 data), (utilizing time 4 data). Key words: Instructional, Manuscripts of Ulu Jambau.